Introducing information literacy and careers in librarianship to New York City high school students: a case report. - Hickner, Andy; Delgado, Diana; Boyle, Jessica; Holden, Lynne; Jewell, Sarah; Wood, Michael A.; Wheeler, Terrie R. (Journal of the Medical Library Association, 2026)
Background: Black, Indigenous, and People of Color (BIPOC) are underrepresented in librarianship. We developed a curriculum to introduce high school students from BIPOC communities to careers in health sciences librarianship and to concepts and skills in health information literacy. Case Presentation: Librarians at Weill Cornell Medicine partnered with Mentoring in Medicine, a Bronx-based nonprofit, to develop the Community Health Ambassador Program (CHAmP) curriculum. The project settings were at three New York City schools. The project took place over two years, with the pilot taking place in year 1, followed by an assessment which included data from pre- and posttests measuring student learning and focus groups with the students to gather feedback about their experience. Informed by data from the year one assessment, we worked with an experienced high school teacher to redesign the curriculum for year 2. Changes included reducing the amount of lecture and providing more time for activities to reinforce the content, including a team final project and presentations. In year two focus groups, students demonstrated increased understanding of health sciences librarianship and indicated increased engagement and enjoyment of the course compared to year 1. There was a statistically significant improvement in the mean student score from the pretest to the posttest. Conclusions: The revised curriculum resulted in increased student engagement and statistically significant improvement in learning compared to the year one pilot. We have published the full curriculum online under a Creative Commons license so that other organizations may implement it in their communities.